Climate adaptation, technological self-reliance, and the developing world: Evidence from an emerging economy - Calzado, Rodolfo (Animo Repository, 2017)
Despite good intentions, development assistance from donor countries are often underutilized by recipient nations due to weak absorptive capacities. Addressing this issue has become more imperative with recent international accords engendering the rapid influx of massive climate assistance funds into the developing world. Particularly, interventions are focused on addressing exceptional vulnerabilities of developing nations to near-term climate impacts, for example, devastating typhoons and associated hazards. Fundamental to this effort is establishing the necessary technology infrastructure for generating quality climatic and environmental information, which serves as valuable logistical support for Disaster Risk Reduction and Management plans and activities. Efforts to address this in developing countries, however, are often sluggish or met with gridlocks. This is despite following internationally-prescribed best-practice roadmaps, conditioned by access to foreign aid. The Philippines’ experience in implementing its technological self-reliance policy provides a possible framework for overcoming this difficulty. Contribution analysis, through dissecting and examining the policy implementation period of 2010–2015, reveals that a more cooperative sociopolitical landscape, engendered by the visibility of a program “championing” the country’s drive to break away from technological dependence, can provoke rapid technological catch-up, bringing about the desired transformation. © 2017 by De La Salle University.